2008
DOI: 10.1128/aac.00785-07
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Chlamydia trachomatis to the Excipient Hydroxyethyl Cellulose: pH and Concentration Dependence of Antimicrobial Activity

Abstract: Hydroxyethyl cellulose (HEC) is used as a neutral excipient in microbicides used against sexually transmitted pathogens. However, HEC inhibits the infection of cervical epithelial cells by Chlamydia trachomatis at pH 5 in a concentration-dependent manner. At pH 7, infection is inversely dependent on the concentration of HEC, possibly due to pH-dependent calcium sequestration.Chlamydia trachomatis causes pelvic inflammatory disease, ectopic pregnancy, and reproductive disability and is the most common bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
1
2
2
Order By: Relevance
“…Interestingly, our results differ from those of Sater et al (13), who used the lymphogranuloma venereum strain C. trachomatis L2 and showed concentration-and pH-dependent inhibitory effects of HEC on chlamydial growth in vitro. However, there are important differences between the two studies, including the fact that we used a complex buffer that may better mimic the physicochemical properties of the vaginal fluid than the phosphate and acetate buffers used by Sater et al Moreover, we observed the growthenhancing effect at 0.75% to 1.5% wt/vol (7,500 -15,000 g/ml) HEC concentrations, which are common in the vaginal gels (7,14), whereas Sater et al used significantly lower HEC concentrations (2-200 g/ml).…”
contrasting
confidence: 99%
“…Interestingly, our results differ from those of Sater et al (13), who used the lymphogranuloma venereum strain C. trachomatis L2 and showed concentration-and pH-dependent inhibitory effects of HEC on chlamydial growth in vitro. However, there are important differences between the two studies, including the fact that we used a complex buffer that may better mimic the physicochemical properties of the vaginal fluid than the phosphate and acetate buffers used by Sater et al Moreover, we observed the growthenhancing effect at 0.75% to 1.5% wt/vol (7,500 -15,000 g/ml) HEC concentrations, which are common in the vaginal gels (7,14), whereas Sater et al used significantly lower HEC concentrations (2-200 g/ml).…”
contrasting
confidence: 99%
“…1B). This proportionality between the concentration and the inhibitory effect supports a previously suggested mechanism for HEC inhibition, that HEC may act as a competitive inhibitor by competing with the host cell for the recognition site on the chlamydial surface (20).…”
Section: Validation Of Ibachie With Known Chemical Inhibitorssupporting
confidence: 56%
“…Although excipients are typically used as delivery vehicles and are expected to be pharmacologically inactive, a 90-kDa HEC has been shown to have an inhibitory effect on C. trachomatis infection, purportedly as a competitive inhibitor for adhesion (20). When EBs were treated with HEC, the inhibitory effect of HEC was directly proportional to its concentration in the range of 0.175% to 0.7% and reached complete inhibition at 1.4% (Fig.…”
Section: Validation Of Ibachie With Known Chemical Inhibitorsmentioning
confidence: 93%
See 1 more Smart Citation
“…2-methoxystipandron (8) did not show any antiviral effect at the non-toxic concentration of 6.25 µM (data not shown). In vitro and in vivo monitoring of the effect of hydroxyethyl cellulose a major gelling agent of vaginal gels on C. trachomatis growth.Interestingly, our results are different from those of Sater et al[147], who used the lymphogranuloma venereum strain C. trachomatis L2 and showed a concentration-and pHdependent inhibitory effect of HEC on chlamydial growth in vitro. However, there are important differences between the two studies, including the fact that we used a complex buffer which may mimic better the physicochemical properties of the vaginal fluid than the phosphate and acetate buffers used by Sater et al.…”
contrasting
confidence: 99%